1993
DOI: 10.1002/pssa.2211390110
|View full text |Cite
|
Sign up to set email alerts
|

Structure and phase-change phenomena in evaporated thin films of cobalt phthalocyanine

Abstract: The structures of thin films of cobalt phthalocyanine (CoPc) which have been deposited onto glass substrates at room temperature are investigated. Films of thickness 0.1 μm are primarily of the α‐form and show a single Bragg peak indicating a strong preferential orientation in either the [001] or [200] directions, depending on whether the structure is tetragonal or orthorhombic. Films of thickness 1 μm show a slight decrease in the degree of preferential orientation, with the appearance of several additional p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 27 publications
4
25
0
Order By: Relevance
“…However because of that, it is impossible to assert unequivocally that the resulting layer of CoPcF 4 has the same crystalline phase as polycrystalline CoPcF 4 . It is known [22,23] that CoPc can be deposited on the substrate in two possible crystal phases -metastable α-phase (Fig. 2a) and stable β-phase (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However because of that, it is impossible to assert unequivocally that the resulting layer of CoPcF 4 has the same crystalline phase as polycrystalline CoPcF 4 . It is known [22,23] that CoPc can be deposited on the substrate in two possible crystal phases -metastable α-phase (Fig. 2a) and stable β-phase (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although there has been no report on ␣-MnPc, it is known that ␣-type crystals are obtained by deposition of several kinds of MPc. In fact Gould et al reported that the deposition films of copper phthalocyanine 22 and cobalt phthalocyanine 23 have ␣-type crystal structure and that they transform to ␤-type crystals by thermal annealing. It is shown theoretically that ␣-type crystals have lower surface energy and higher bulk energy than ␤-type ones for square planar MPc's, 24 which supports our speculation on the polymorph of the deposited MnPc films.…”
Section: Magnetic Properties Of Disordered Mnpc Filmsmentioning
confidence: 99%
“…However, if ␤-form evaporated onto substrates at room temperature, the ␣-form is normally obtained. Moreover, transformations from ␣ form to ␤ form using successive sublimation [4,5] or thermal annealing at a temperature range of 473-573 K [6] have been reported. Recently, El-Nahass et al [7] have reported that the conversion from ␣-NiPc to ␤-NiPc is occurred at 623 K by thermal annealing.…”
Section: Introductionmentioning
confidence: 99%